Transcranial Auricular Vagus Nerve Stimulation (taVNS) and Ear-EEG: Potential for Closed-Loop Portable Non-invasive Brain Stimulation - Ruhnau, Philipp; Zaehle, Tino (Frontiers in Human Neuroscience, 2021)
No matter how hard we concentrate, our attention fluctuates - a fact that greatly affects our success in completing a current task. Here, we review work from two methods that, in a closed-loop manner, have the potential to ameliorate these fluctuations. Ear-EEG can measure electric brain activity from areas in or around the ear, using small and thus portable hardware. It has been shown to capture the state of attention with high temporal resolution. Transcutaneous auricular vagus nerve stimulation (taVNS) comes with the same advantages (small and light) and critically current research suggests that it is possible to influence ongoing brain activity that has been linked to attention. Here, we review current work on ear-EEG and taVNS and suggest that a combination of the two methods in a closed-loop system could serve as a potential application to modulate attention.